Effect of scapular retraction exercise on forward head posture among university students - Tay, Kai Wei (2022)
Background and Objective: Forward head posture (FHP), an abnormal alignment of the neck that is developed the muscle imbalance on the agonist and antagonist muscle of the shoulder which might further result in pain and deterioration of quality of life. Moreover, several studies show a high prevalence of forward head posture problem in university students. Despite this, the number of studies is limited and difference in methodology, study populations and study settings. Therefore, this study is conducted to investigate the effects of scapular retraction exercise intervention to determine the effects if it is significant although there are different methodology, population, and settings. The objective of this study is to determine the effects of scapular retraction exercises on forward head posture among university students. Methods: This study was a single subject (AB design), randomized, experimental study. The sampling method was convenience sampling, with sample size calculated to be at 60. The targeted participant were university students. Participants were randomized into 2 groups, the intervention group, and the control group. Postural alignment assessment was used to assess baseline characteristics and inclusion criteria. All participants in the intervention group underwent a 4-week scapular retraction exercise consisting of 5 different exercises plus ergonomic advice. On the other hand, all participants in the control group were only given ergonomic advice. There were 2 post-treatment postural assessment using the postural alignment assessment tool, at the end of second week and fourth week. The difference between the craniovertebral angle during pre-treatment and post-treatment was calculated. Results: The total participants were only 52 university students; thus, their result data is processed. Firstly, the prevalence of forward head posture among university student was 48% after screening of 130 recruited participants. Moving to the effects of scapular retraction exercise, week 2 and week 4 post-treatment CVA was assessed. Significant effect on forward head posture was found within group of intervention group (scapular retraction exercise plus ergonomic advice) at week 2 and week 4. Gender differences and BMI category was also tested in between groups with the week 4 post-treatment CVA, no significant difference was found. Ultimately, III between groups result also proved to have significant difference between intervention and control group with the week 4 post-treatment CVA. All in all, this study proved that there was a significant effect of scapular retraction exercise on forward head posture among university students. Conclusion: This current study concluded that a 4-week scapular retraction exercise was effective on treating forward head posture among university students. A simple, effective, and convenient set of scapular retraction exercise intervention was proven, as it aims to contribute to the physiotherapy field and the knowledge of intervention in treating forward head posture.